Necrotizing Fasciitis Due to Acinetobacter baumannii Complex Following Body Contouring Surgery: First Case Report - Lázaro Cárdenas-Camarena, MD; Cristopher Cárdenas-Cruz, MD; Iván González Godínez, MD (Plastic and Reconstructive Surgery, Global Open)
Summary:. The rise in aesthetic surgery in recent years has led to an increased incidence of complications associated with these procedures. Liposuction and autologous fat transfer have become some of the most common cosmetic interventions worldwide, also raising the risk of developing postoperative infections, including those caused by multidrug-resistant Gram-negative bacilli, which can be life-threatening. We present the case of a 40-year-old woman who developed septic shock secondary to deep necrotizing fasciitis in the right thigh following liposuction and autologous fat transfer to the buttocks. During the postoperative period, she developed a necrotizing soft tissue infection affecting the right thigh and buttock, which progressed to necrotizing fasciitis. The patient required surgical debridement, fasciotomy, and combined antibiotic therapy. Tissue cultures revealed multidrug-resistant Acinetobacter baumannii complex haemolyticus, sensitive to carbapenems. The patient had surgical debridement and a 14-day course of antibiotics, resulting in clinical recovery. A. baumannii is a significant cause of nosocomial infections worldwide, and its persistence on inanimate surfaces may be underestimated. Complications such as necrotizing soft tissue infections are typically caused by Gram-positive microorganisms such as methicillin-resistant Staphylococcus aureus and Gram-negative fermenting enterobacteria. The isolation of A. baumannii in soft tissue cultures is unusual, making this case notable, as necrotizing soft tissue infections caused by this nonfermenting Gram-negative bacillus have not been previously reported following aesthetic body contouring surgery.